The influence of the structure and properties of powder heat-resistant alloys on the features of 3D printing of products from them - Duriagina Zoia; Lemishka Ihor; Ovchynnykov Oleksandr; Yefanov Vladimir; Klimczyk Piotr (MATEC Web of Conferences, 2024)
Methods of fractional analysis of powders based on heat-resistant nickel alloys, electron microscopy and elemental analysis, study of bulk density of powder fractions, as well as approaches of mathematical modeling of packing density were applied in the work. Spherical powders based on heat-resistant nickel alloys of two different fractions: 50...200 μm and ≤63 μm were studied. The morphology of the surface of spherical particles of powders based on heat-resistant nickel alloys of different fractional composition, as well as their granulometric characteristics, was researched. It is shown that as the fractional composition of powder fractions decreases, their homogeneity and bulk density increase. At the same time, it was established that more finely dispersed fractions are characterized by worse fluidity indicators. According to the simulation results, the optimal fractional composition of the powder for filling the previously specified volume was determined. It is shown that as the size of the investigated particles decreases, their packing density increases.